Social skills and behavior children in a Basic Education Unit of Buena Fe canton, Los Ríos province, Ecuador - Cárdenas-Loor , Alexandra (2021)
Social skills were assessed and behavior in children 3 to 5 years of age. The research was carried out at the “TIWINZA” Basic Education School, located in Buena Fe canton, Los Ríos province. The abilities of 16 children were studied through surveys of their parents or legal representatives, and for this purpose the survey proposed by Merrell (1994) was used. 87% and 75% of the children were located within a medium level of cooperation, interaction and social independence. Regarding social skills, 75% of the children were between the medium and significant deficit levels. 62.5%, 56.3%, and 37.5 did not present problems of social isolation, anxiety/complaints, or selfish or egocentric behavior, respectively, and only one student showed a significant problem. Finally, 56% of children express their emotions easily. These findings indicate that most of the children studied did not present significant behavioral problems.